There was a little girl - McBain, Ed (New York, NY : Warner Books, 1994)
After Matthew Hope slips into a coma--the result of a drive-by shooting--his friends, private eye Warren Chambers and police detective Morris Bloom--must follow in his investigative footsteps to discover why he was shot. All signs point to the local circus--an underworld of offbeat sex, drugs, blackmail, murder, and in the center of it all, there was a little girl.
Keywords: Hope, Matthew (Fictitious character); Lawyers -- Florida; Lawyer detectives; Murder; Florida; Mystery fiction; Legal stories